2018
DOI: 10.1038/s41598-018-29855-z
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Red Blood Cell Distribution Width and Sarcopenia in U.S. Adults

Abstract: One pathophysiological sign of sarcopenia is chronic inflammation. Given that levels of red blood cell distribution width (RDW) are increased in chronic inflammation, we evaluated the association between increased RDW and sarcopenia among adults in the general U. S. population and analyzed data from 11,761 participants from the National Health and Nutrition Examination Survey (NHANES) 1999–2006. Sarcopenia was defined as an appendicular skeletal muscle mass (ASM) divided by weight (%) that was less than one st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 40 publications
2
24
0
1
Order By: Relevance
“…Further, Kim et al has previously proven that RDW has a positive correlation with sarcopenia, and our data also showed a significant increase in RDW in the sarcopenia group when comparing sarcopenia and non-sarcopenia groups (Figure 5A) [4].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Further, Kim et al has previously proven that RDW has a positive correlation with sarcopenia, and our data also showed a significant increase in RDW in the sarcopenia group when comparing sarcopenia and non-sarcopenia groups (Figure 5A) [4].…”
Section: Discussionsupporting
confidence: 81%
“…However, in recent years, CT images and MRI tomographic images have been used as methods to calculate decreases in muscle mass and are highly evaluated for objectivity and accuracy [3]. Moreover, as an evaluation method of sarcopenia other than imaging, Kim et al suggested red cell distribution width (RDW), which is usually used to determine variability in the size of circulating erythrocytes [4]. They reported that RDW might reflect the existence of chronic inflammation, which is one of the major causes of sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…This ineffective erythropoiesis may in turn lead to reduced red cell size (i.e., decreased MCV) as well as a greater red cell size distribution (i.e., increased RDW), which is consistent with that found by Vuong et al with their obese participants [57]. As well, epidemiologic studies suggest that RDW is associated with increased levels of CRP and may be a predictor of chronic diseases and mortality in cardiovascular disease, cancer, and other diseases [58]. However, we only saw a weak correlation between RDW and CRP (R = 0.19187).…”
Section: Blood Cells In the Obese Cohortsupporting
confidence: 86%
“…Higher levels of RDW might be due to subacute inflammation[ 8 ] (accompanying, causing, or exacerbating vascular disease), disease-related nutritional deficiencies resulting in altered hematopoiesis,[ 31 , 32 ] or abnormal production and/or survival of circulating erythrocytes (perhaps reflecting occult systemic illness). However, we did not have data to evaluate these possibilities and thus these suggestions are speculative.…”
Section: Discussionmentioning
confidence: 99%